2015
DOI: 10.1002/rnj.160
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Cardiac Rehabilitation Program on Exercise Capacity, Quality of Life, and Functional Status of Coronary Artery Disease Patients with Left Ventricular Dysfunction

Abstract: Cardiac rehabilitation practitioners should encourage patients to attend to and be compliant in the rehabilitation programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 16 publications
1
17
0
3
Order By: Relevance
“…6 Data from Iran corroborate the benefits of CR. [7][8][9][10] Unfortunately, CR is underused, particularly when compared with other secondary prevention recommendations for CVD. 11 Studies conducted in Iran also demonstrate gross under-referral, enrolment, adherence and completion.…”
Section: Introductionmentioning
confidence: 99%
“…6 Data from Iran corroborate the benefits of CR. [7][8][9][10] Unfortunately, CR is underused, particularly when compared with other secondary prevention recommendations for CVD. 11 Studies conducted in Iran also demonstrate gross under-referral, enrolment, adherence and completion.…”
Section: Introductionmentioning
confidence: 99%
“…Post-CR exercise tolerance and functional capacity increased in both obese and non-obese patients, however, this increase was more significant in the non-obese group. In a study evaluating post-CR exercise capacity and quality of life in patients with left ventricular dysfunction, the MET values increased from 8.00 ± 2.56 to 10.08 ± 3.00 MET, with a significant improvement in the SF-36 physical and psychological component of the patients [29]. In our study, we observed a significant difference in the MET values and quality of life scales of both groups of patients, however, the increase in MET values was more prominent in the non-obese group.…”
Section: Discussionmentioning
confidence: 99%
“…De hecho, solo 67 de los posibles 760 pacientes que iniciaron el programa cumplieron con los criterios de inclusión. A diferencia de lo que ocurre en diversos otros estudios [22][23][24][25] el presente estudio no incluye a pacientes no cardiópatas en prevención primaria. Así mismo, el programa de rehabilitación fue riguroso, efectuado en un solo centro por un número reducido de profesionales y con una evaluación tan objetiva como era posible.…”
Section: Discussionunclassified